Sociology of Educational Institutions: Motivation And Influence of Socioeconomic Status on Student Involvement in PKBM Ar-Rosyid Purwokerto - Nadilatur Rofiqoh; Irkham Auladi; Moh. Hanif (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research is motivated by the fact that there is still a gap in student involvement influenced by the socioeconomic status (SSE) of families in non-formal educational institutions. The study aims to analyze the influence of SSE on student motivation and engagement in PKBM Ar Rosyid Purwokerto, identify the factors that mediate these relationships, and explore institutional strategies in reducing learning participation gaps. The research uses a qualitative approach with a single case study design anchored. The data source consisted of 3 homeroom teachers, 12 students from the low, medium, and high SSE categories, the head of PKBM, and 3 parents who were selected through purposive sampling and snowball sampling techniques. Data were collected through participatory observations, semi-structured interviews, document analysis, and field notes. Data analysis uses the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and conclusion drawn. The validity of the data was tested through source triangulation and triangulation techniques. The results of the study show that students from low SSE face obstacles in the form of limited learning facilities, access to technology, and family economic pressures that have an impact on learning engagement. However, family support, teacher attention, and positive relationships between students can increase learning motivation. This study also found that a culture of social care through peer mentoring, psychological mentoring, and affirmative policies of PKBM plays an important role in reducing the impact of socio-economic